Can Binaural Beat Music Be Useful as a Method to Reduce Dental Patients' Anxiety? - Negareh Salehabadi; Amirhossein Pakravan; Reza Rasti; Mehdi Pourasghar; Seyyed Jaber Mousavi; Mohammad Ebrahimi Saravi (Elsevier, 2024)
Background: One of the main issues in dentistry and a barrier to offering dental treatment is anxiety. The usage of music is one of the nonmedical ways to reduce anxiety. Binaural beat technology is used as a music treatment technique. The goal of this study wasto determine whether employing binaural beat technology during and after dental appointments can help patients feel less anxiety and pain. Methods: In this clinical trial, 80 patients who were candidates for mandibular wisdom tooth surgery (in 2 test and control groups) were examined. In the control group, after the injection of anaesthesia and before surgery, they waited for 10 minutes and during this time no intervention was done. In the test group, thought, after the injection of anaesthesia, the patients were asked to listen to binaural beat music with headphones for 10 minutes. The level of anxiety of the patients before and after the intervention was checked with the Spielberger State-Trait Anxiety Inventory and finally the data were entered into SPSS version 21 software. Results: The score of overt anxiety (P = .524) and covert anxiety (P = .118) before the start of the study was not significant between the 2 groups, but overt anxiety (P = .001) and covert anxiety (P = .000) after the intervention in the test group decreased significantly. Conclusions: The research showed that the use of binaural beat music has significantly reduced the level of overt and covert anxiety in patients and can be used as an alternative nonpharmacologic method to reduce anxiety.